O Tribunal Superior do Trabalho e o meio ambiente do trabalho: análise qualitativa da jurisprudência relativa ao trabalho em minas - ROCHA, Maria de Nazaré Medeiros (Universidade Federal do Pará, 2017)
The present paper aims to analyze the performance of the Superior Labor Court (“TST”) through its case law on workplace environment, particularly concerning mining work, pursuant to identify the points of compatibility and / or incompatibility with the doctrinal protection given to the workplace environment. For this paper we used cases selected by the TST’s Jurisprudence Coordination, in consequence of Resolution n° 96 of the Supreme Council of the Labour Court, adopted in March 24th, 2012, that institutionalized the Safe Work Program. The Coordinator of Jurisprudence of the TST determined the criteria in which the categories were separated. The chosen period comprised from 2000 to the first quarter of 2013, and it was used as search criteria the term "Mining Companies" with several key cases, such as: i) outsourcing of mining activities; ii) subsidiary liability of the mining company when there are services related to its core business; iii) implementation of strict liability in case of accidents at the workplace, since mining is considered a risk driven activity; iv) impossibility of “Collective Norm” to reduce the deadline established in the art. 118 of Federal Law n° 8.213/1991; v) suppression of any breaks provided in art. 298 of the Labor Code; vi) establishment of a proportionate system - based on the length of exposure to outstanding risk - for the compliance with the mandatory additional hazard payment; vii) impossibility of compensation or extension of working hours without permission of the competent authority on hygiene and safety; and, finally, viii) non observance of the provisions of art. 58, § 1 of the Labor Code or of the Ruling n° 366/TST in regards to the time spent by the employees to move from the beginning of mine to their workplace and vice versa. Based on the results of such research, it was identified the most common arguments listed in the cases, referring to the protection of the workplace environment.